2015
DOI: 10.1530/eje-14-1152
|View full text |Cite
|
Sign up to set email alerts
|

Early endocrine alterations reflect prolonged stress and relate to 1-year functional outcome in patients with severe brain injury

Abstract: Objective: Severe brain injury may increase the risk of developing acute and chronic hypopituitarism. Pituitary hormone alterations developed in the early recovery phase after brain injury may have implications for long-term functional recovery. The objective of the present study was to assess the pattern and prevalence of pituitary hormone alterations 3 months after a severe brain injury with relation to functional outcome at a 1-year follow-up. Design: Prospective study at a tertiary university referral cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 46 publications
(52 reference statements)
3
17
0
Order By: Relevance
“…TSH is a glycoprotein hormone secreted in the anterior pituitary and is responsible for stimulating metabolism of tissue throughout the body. Decreased TSH, referred to as hypothyroidism, results in weight gain, and is a common symptom of TBI survivors (15, 62, 63, 64). In a prospective study assessing functional outcome in patients with TBI, 32% presented hypothyroidism at 3months postinjury (62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TSH is a glycoprotein hormone secreted in the anterior pituitary and is responsible for stimulating metabolism of tissue throughout the body. Decreased TSH, referred to as hypothyroidism, results in weight gain, and is a common symptom of TBI survivors (15, 62, 63, 64). In a prospective study assessing functional outcome in patients with TBI, 32% presented hypothyroidism at 3months postinjury (62).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased TSH, referred to as hypothyroidism, results in weight gain, and is a common symptom of TBI survivors (15, 62, 63, 64). In a prospective study assessing functional outcome in patients with TBI, 32% presented hypothyroidism at 3months postinjury (62). This parallels a longitudinal follow-up of adults with TBI showed over a median period of 38months, 42% of TBI patients had gained weight (65).…”
Section: Discussionmentioning
confidence: 99%
“…Marina et al found in their study that endocrine alterations measured at a median of 3.3 (range 2.1‐4.9) months after an acquired severe brain injury reflected prolonged stress and were related to poorer one‐year functional outcome in patients with a severe brain injury . Baseline cortisol levels did not differ between patients with TBI and controls, but elevated stress hormones (eg, 30‐min stimulated cortisol, prolactin, and/or IGF1) and suppressed gonadal and/or thyroid function were concomitantly recorded in 68% of the patients three months after the injury.…”
Section: Introductionmentioning
confidence: 96%
“…Baseline cortisol levels did not differ between patients with TBI and controls, but elevated stress hormones (eg, 30‐min stimulated cortisol, prolactin, and/or IGF1) and suppressed gonadal and/or thyroid function were concomitantly recorded in 68% of the patients three months after the injury. They suggested that endocrine alterations, similar to secondary hypogonadism and hypothyroidism, after an acquired severe brain injury most probably reflected a prolonged stress response rather than pituitary insufficiency per se …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation